2019
DOI: 10.1007/s00425-019-03316-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of polyphenols and inhibition of photosystem II under acute photooxidative stress

Abstract: Main conclusionWe observed a close correlation between the inhibition of photosystem II and the oxidation of polyphenols during an acute oxidative stress in sunflower leaf discs.To assess the physiological significance of polyphenols as antioxidants in planta, we compared the kinetics of polyphenols oxidation with the inhibition of the photosynthetic apparatus in sunflower leaf discs exposed to an acute photooxidative stress. Illumination of leaf discs in presence of methyl viologen induced a rapid and large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(72 reference statements)
2
1
0
1
Order By: Relevance
“…For example, decreased photosystem II efficiency and net photosynthesis in the DFRi plants (Figure 3b,c) indirectly supports the proposal that condensed tannins participate in regulation of the oxidative state of photosynthetic cells (Gourlay & Constabel, 2019;Harding, 2019). This functionality would fit the suggested polymerization of condensed tannins in chloroplast-derived tannosomes (Brillouet et al, 2013) and the recently identified links between polyphenol oxidation and acute oxidative stress in chloroplasts of Helianthus annuus L. (Samson et al, 2020).…”
Section: Betula Pendulasupporting
confidence: 79%
“…For example, decreased photosystem II efficiency and net photosynthesis in the DFRi plants (Figure 3b,c) indirectly supports the proposal that condensed tannins participate in regulation of the oxidative state of photosynthetic cells (Gourlay & Constabel, 2019;Harding, 2019). This functionality would fit the suggested polymerization of condensed tannins in chloroplast-derived tannosomes (Brillouet et al, 2013) and the recently identified links between polyphenol oxidation and acute oxidative stress in chloroplasts of Helianthus annuus L. (Samson et al, 2020).…”
Section: Betula Pendulasupporting
confidence: 79%
“…Although inhibition of ATP synthesis can also result from the inactivation of the F-ATPase and from the inhibition of the photosynthetic electron transport, only the uncoupling of thylakoids can cause an inhibition of non-photochemical quenching (qN) accompanied by an overreduction of the photosynthetic electron transport chain (i.e., a decrease of photochemical quenching qP). Such simultaneous decreases of both qN and qP have been reported in a variety of environmental stresses: low temperatures (Strand and Öquist 1988), ozone (Calatayud et al 2002), copper (Pádua et al 2010), acid rain (Qiu and Liu 2002), and methyl viologen (Samson et al 2020). To further support our conclusions, it would have been interesting to directly measure the inhibition of qN formation in thylakoids treated with low to moderate AAPH concentrations.…”
Section: R a F Tsupporting
confidence: 77%
“…The high daily turnover of quercetin and luteolin derivatives observed here poses the question whether the flavonoids have been degraded because of the combined action of high light and elevated leaf T [ 91 ] or have instead been oxidized by the excess of ROS (or through electron donation to vacuolar peroxidase)and not fully recycled to their reduced forms [ 77 , 92 , 93 ]. Addressing this complex issue requires further investigations aimed at exploring changes in both the sub-cellular distribution of ascorbate (and glutathione as well) [ 94 , 95 ] and the activity of mono-dehydroascorbate [ 93 ] in leaves facing severe drought stress.…”
Section: Discussionmentioning
confidence: 99%